Erodibility and sedimentation potential of marly formations at the watershed scale - F. Rostami; S. Feiznia; M. Aleali; M. Heshmati; B. Yousefi yegane (Global Journal of Environmental Science and Management)
Grupi and Kashkan marl formations comprise a considerable part of Zagros region. These formations have a considerable erodibility and sedimentation potential because of their special geological and mineralogical characteristics. The objective of this study was to compare the erosion and sediment yield of Kashkan and Grupi formations in Merk watershed located in southeast Kermanshah, using the Modified Pacific Southwest Inter-Agency Committee model. This model is suitable for estimating erosion and sediment intensity within each geomorphologic unit comprising nine effective environmental factors as geological, pedological, climate, runoff, topography, land cover, land use, surface, and river erosion factors. The results indicated that Kashkan formation comprises siltstone, sandstone, shale, and conglomerate, and Grupi formation contains shale, clay, and limestone with a high erodibility potential. Field measurements and soil samples analyzed for effective factors releaved that sediment yield for Merek watershed was 18080.6 m3/ha/y. Furthermore, field measurement and soil samples analyzed for effective factors releaved that sediment yields for Kashkan and Gurpi were 7243.3 and 10837.5 m3/ha/y, respectively. The reasons for erosion intensity and sedimentation in the two mentioned formations are slopes, vegetation and land use in addition to the type of rocks in Kashkan and Gurpi formations which are predominantly marl and shale.